(untitled) (Educational Knowledge, 2018)
This literature review explores a series of support strategies that specifically guide teachers on different options for adapting the curriculum to meet the educational needs of students with visual impairments. The methodological process employed was based on a descriptive review, using a phased approach to search for, organize, select, and analyze information relevant to the topic. From this perspective, theoretical proposals are presented regarding the relationship between visual impairment and cognition, as well as various criteria for adjusting the educational plan to effectively address the diverse needs of students in accessing the teaching and learning process under equitable conditions. Similarly, the description of practices related to guidelines for allocating support during the evaluation process is highlighted as a significant contribution, recognizing it as a key component of the right to a quality education.